Keragaman dan Daya Hambat Spora Tular Udara yang Mengkontaminasi Media Baglog Jamur Tiram (Pleurotus ostreatus (Jacq. ex Rr) Kummer) - SUDARMA, I MADE; PUSPAWATI, NI MADE; DARMIATI, NI NENGAH; YULIADHI, KETUT AYU; SUNITI, NI WAYAN; BAGUS, I GUSTI NGURAH; WIJAYA, I NYOMAN; WIDANINGSIH, DWI (Agrotrop : Journal on Agriculture Science, 2015)
Diveristy and Inhibition of Air-Borne Spores That Contaminate Substrat of OysterMushroom (Pleurotus ostreatus (Jacq. Ex Fr) Kummer). The aim of research to know thediversity, prevalence and inhibition of air-borne spores that could potentially contaminatesubtsrat baglog of oyster mushrooms. In this study using the method: (1) the arrest of sporescarried out during the hours of 7 am to 13 pm by placing three petri dish that already containsmedia PDA 3 pieces, and repeated 3 times, (2) inhibition ability of air-borne spores againstoyster mushroom. The place and time of the study conducted at Jl. Siulan Gang Zella No. 7Denpasar, and implemented in October 2014 to February 2015. The results showed that 13genera, including Aspergillus spp, as many as 10 with a prevalence of 13.51%, Aspergillusniger 7 (9.45%), Brachysporium sp., 1 (1.35%) , Cunninghamella sp. 1 (1.35 %), Fusariumspp. as many as 19 (25.6 %), Giotrichum sp. 1 (1.35%), Mucor spp. , a total of 18 (24.32%),Neurospora spp., as many as 8 (10.81%), Penicillium spp. 2 (2.70%), Phytophthora spp. 4(5.40%), Stachybotrys sp. 1 (1.35%), Trichoderma sp. 1 (1.35%) and Umbelopsis sp. 1 (1.35%). The highest prevalence achieved by Fusarium spp . amounting to 25.67 %, followed byMucor spp. 24.32%. Diversity index (H') was obtained from each replicate of 0.6438, 0.7048,0.5611 with a 0.6366 average. Dominance index (C) obtained by 0.6331. 0.8646, 0.6146, andaverage 0.7041. Diversity including < 1, marked by low diversity and dominance index closeto 1, meaning there is dominance. The dominance held by Fusarium spp . and Mucor spp.Inhibitory effects of air -borne fungi on the growth Oyster mushroom in vitro; The highestachieved by Fusarium spp, with inhibition of 94.00 ± 1.2%, followed by Aspergillus spp.amounting to 92.15 ± 1.5%, and the lowest was achieved by Penicillium spp . amounting to70.37 ± 2.5%.
Keywords: prevalence; diversity; inhibition ability; air-borne spores, and fungal contaminant